Anmeldelser - Røllum-Larsen, Claus (Danish Yearbook of Musicology, 1999)
Review of: Paul Rapoport: The Compositions of Vagn Holmboe. A Catalogue of Works and Recordings with Indexes of Persons and Titles. Edition Wilhelm Hansen, København 1996.